Advances in Solidification Technologies of Lunar Regolith-Based Building Materials Under Extreme Lunar Environments - Jun Chen; Ruilin Li (Buildings, 2025)
With the launch of the Artemis program and the International Lunar Research Station project, the construction of lunar bases has emerged as a global research focus. In situ manufacturing technologies for robust lunar regolith-based building materials are critical to ensuring building safety under the Moon’s extreme environmental conditions. This paper reviews the relevant advancements in two areas: solidification technologies for lunar regolith-based construction materials and simulation techniques of extreme lunar environments. This review reveals that, although significant advancements have been made in solidification technologies, the development of lunar environment simulation technologies, particularly for 1/6 g gravity, has lagged, thereby hindering the assessment of the in situ applicability of these solidification methods. To address these limitations, this paper introduces a newly developed comprehensive lunar extreme environment simulation system based on superconducting magnetic suspension technology and its potential applications in lunar regolith-based construction material solidification. This review highlights the current progress and challenges in solidification techniques for lunar regolith-based building materials, aiming to enhance researchers’ attention to the extreme environmental conditions on the lunar surface.